1995
DOI: 10.1002/cne.903510207
|View full text |Cite
|
Sign up to set email alerts
|

NADPH‐diaphorase active and calbindin D‐28k‐immunoreactive neurons and fibers in the olfactory bulb of the hedgehog (Erinaceus europaeus)

Abstract: The hedgehog, a macrosomatic insectivore with an extraordinary development of the olfactory structures, has a crucial value for any phylogenetic or comparative study in mammals. The distribution pattern and morphology of NADPH-diaphorase-active and calbindin D-28k-immunoreactive neurons were studied in the main and accessory olfactory bulbs of the hedgehog. NADPH-diaphorase (ND) staining was carried out by a direct histochemical method, and the calbindin D-28k (CaBP) immunoreaction by using a monoclonal antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
70
4

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(89 citation statements)
references
References 69 publications
15
70
4
Order By: Relevance
“…Recently several investigators have described the distribution of NOergic neurons in relation to aminergic neurons in different regions of the central nervous system, including the zona inserta 17) , prefrontal cortex 13) , medulla oblongata 21) , hippocampus 37) , cuneate nucleus 35) , olfactory bulb 1) , lateral geniculate nucleus 14) , spinal cord 31) , and cerebral cortex 36) . Nevertheless, little is known about the relationship between NO and neuroactive amino acids in the auditory nuclei.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently several investigators have described the distribution of NOergic neurons in relation to aminergic neurons in different regions of the central nervous system, including the zona inserta 17) , prefrontal cortex 13) , medulla oblongata 21) , hippocampus 37) , cuneate nucleus 35) , olfactory bulb 1) , lateral geniculate nucleus 14) , spinal cord 31) , and cerebral cortex 36) . Nevertheless, little is known about the relationship between NO and neuroactive amino acids in the auditory nuclei.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the above approach has been used widely for mapping NOS-containing (presumably NOergic) neurons in the central nervous system 3,38) . NADPH-d histochemistry has also been combined with immunohistochemistry to assess relationships between the distribu-tion of NO and traditional neurotransmitters in various regions of the CNS 1,14,30,35,37) . Several studies suggest that NO and NOS play a role in audition.…”
Section: Introductionmentioning
confidence: 99%
“…The NADPH-diaphorase (NADPHd) histochemical technique, known to stain specific neurons [Thomas and Pearse, 1964], can selectively stain particular populations of neurons in a Golgi-like manner [Scherer-Singler et al, 1983;Alonso et al, 1995;. Throughout the brain, NADPHd and NOS localizations are identical [Bredt and Snyder, 1992].…”
Section: Organization Of the Urodele Caudal Rhombencephalic Alar Platementioning
confidence: 99%
“…In the common marmoset AOB, the distribution of granule cells also remained unclear [19]. Since it has been documented that NADPH-diaphorase is localized in the granule cells in various animals [1,3,10,15,16], we conjectured that NADPH-diaphorase staining could reveal the distribution of the granule cells in the common marmoset AOB. In the present study, we observed that the granule cells were distributed under the MTL.…”
Section: Discussionmentioning
confidence: 94%
“…These histochemical markers are immunostaining for protein gene product (PGP) 9.5, which is predominantly localized in the mitral/ tufted cells in the rodent [14,22] and dogs [15], and staining for NADPH-diaphorase, which is predominantly localized in the granule cells in various animals [1,3,10,15,16].…”
mentioning
confidence: 99%